Study on the surface forming mechanism of the solid–liquid two-phase grinding fluid polishing pipe based on large eddy simulation. (December 2019) - Li, Junye; Su, Ningning; Wei, Lili; Zhang, Xinming; Yin, Yanlu; Zhao, Weihong
To study the surface forming mechanism of the solid–liquid two-phase abrasive flow processing, the large eddy simulation method was used. Taking a 90° stainless steel elbow as the research object, the action mechanism of the dynamic pressure, wall shear force, flow state of the abrasive flow at different cross-sections, formation of the vortex, and trajectory of the abrasive flow on the inner surface of the elbow with abrasive flow composed of solid-phase silicon carbide and liquid-phase hydraulic oil are discussed. This study explores the distribution characteristics of the flow pattern of solid–liquid two-phase abrasive flow. Moreover, the wear and erosion of the abrasive grain and the wall of the workpiece are discussed. The mechanism of surface formation of solid–liquid two-phase abrasive flow is revealed.